The Effectiveness of Online Media in Improving Vocabulary of English Education Department Student - Siti Mafulah (Program Pendidikan Vokasi Universitas Brawijaya, 2017)
Vocabulary is essential in determining how well students learn to speak, listen, read and write a language. One of the English language learning strategies used to motivate students to learn the English vocabulary is through the media. One medium that can be used is the use of online media. By learning through online media, students are expected to be enthusiastic and motivated to memorize and understand the English vocabulary items. Through this study, the effectiveness of Online Media in improving vocabulary skills in students majoring in English Education was tested.This study applies True Experimental Design, where the sample was 30 respondents experimental group and 30 respondents as the control group taken at random from the entire population. The findings show that the T-test results conducted before treatment was 1.001, while the test results after treatment was 1.667 and T-table shows 2.045. It can be concluded that the results of the final value of the T- test is lower than the value of T- table. In other words, the use of Online Media is less effective for learning English especially in vocabulary learning.